Wastes for imported fill - Sherwood, P. T. (ICE works construction guides., 1987)
This guide concerns the use of mineral wastes as bulk fill in road construction and building work, and the use of both mineral and municipal wastes in land reclamation. It covers the principal materials available and their suitability for particular applications.